Treating Obstructive Sleep Apnea with Hypoglossal Nerve Stimulation - Eastwood, Peter R. (Associated Professional Sleep Societies, LLC, 2011)
BACKGROUND: Reduced upper airway muscle activity during sleep is fundamental to obstructive sleep apnea (OSA) pathogenesis. Hypoglossal nerve stimulation (HGNS) counteracts this problem, with potential to reduce OSA severity. STUDY OBJECTIVES: To examine safety and efficacy of a novel HGNS system (HGNS, Apnex Medical, Inc.) in treating OSA. PARTICIPANTS: Twenty-one patients, 67% male, age (mean ± SD) 53.6 ± 9.2 years, with moderate to severe OSA and unable to tolerate continuous positive airway pressure (CPAP). DESIGN: Each participant underwent surgical implantation of the HGNS system in a prospective single-arm interventional trial. OSA severity was defined by apnea-hypopnea index (AHI) during in-laboratory polysomnography (PSG) at baseline and 3 and 6 months post-implant. Therapy compliance was assessed by nightly hours of use. Symptoms were assessed using the Epworth Sleepiness Scale (ESS), Functional Outcomes of Sleep Questionnaire (FOSQ), Calgary Sleep Apnea Quality of Life Index (SAQLI), and the Beck Depression Inventory (BDI). RESULTS: HGNS was used on 89% ± 15% of nights (n = 21). On these nights, it was used for 5.8 ± 1.6 h per night. Nineteen of 21 participants had baseline and 6-month PSGs. There was a significant improvement (all P < 0.05) from baseline to 6 months in: AHI (43.1 ± 17.5 to 19.5 ± 16.7), ESS (12.1 ± 4.7 to 8.1 ± 4.4), FOSQ (14.4 ± 2.0 to 16.7 ± 2.2), SAQLI (3.2 ± 1.0 to 4.9 ± 1.3), and BDI (15.8 ± 9.0 to 9.7 ± 7.6). Two serious device-related adverse events occurred: an infection requiring device removal and a stimulation lead cuff dislodgement requiring replacement. CONCLUSIONS: HGNS demonstrated favorable safety, efficacy, and compliance. Participants experienced a significant decrease in OSA severity and OSA-associated symptoms. CLINICAL TRIAL INFORMATION: Name: Australian Clinical Study of the Apnex Medical HGNS System to Treat Obstructive Sleep Apnea. Registration Number: NCT01186926. URL: http://clinicaltrials.gov/ct2/show/NCT01186926. CITATION: Eastwood PR; Barnes M; Walsh JH; Maddison KJ; Hee G; Schwartz AR; Smith PL; Malhotra A; McEvoy RD; Wheatley JR; O'Donoghue FJ; Rochford PD; Churchward T; Campbell MC; Palme CE; Robinson S; Goding GS; Eckert DJ; Jordan AS; Catcheside PG; Tyler L; Antic NA; Worsnop CJ; Kezirian EJ; Hillman DR. Treating obstructive sleep apnea with hypoglossal nerve stimulation. SLEEP 2011;34(11):1479-1486.